Answer
y = f(x) = 3x - 1
Step-by-step explanation
The general form of the equation in point-slope form is
y - y₁ = m (x - x₁)
where
y = y-coordinate of a point on the line.
y₁ = This refers to the y-coordinate of a given point on the line
m = slope of the line.
x = x-coordinate of the point on the line whose y-coordinate is y.
x₁ = x-coordinate of the given point on the line
Two lines that are parallel to each other have the same slope.
If the equation of a straight line is written in the form of y = 3x - 6,
,The slope and y-intercept form of the equation of a straight line is given as
y = mx + c
where
y = y-coordinate of a point on the line.
m = slope of the line.
x = x-coordinate of the point on the line whose y-coordinate is y.
c = y-intercept of the line.
So, in y = 3x - 6, the slope = m = 3
So, using the point-slope form,
y - y₁ = m (x - x₁)
m = 3
(x₁, y₁) = (2, 5)
x₁ = 2, y₁ = 5
y - y₁ = m (x - x₁)
y - 5 = 3 (x - 2)
y - 5 = 3x - 6
y = 3x - 6 + 5
y = 3x - 1
In function notation, y = f(x)
So, the equation of the line required is
y = f(x) = 3x - 1
Hope this Helps!!!